American and Canadian therapists' perspectives of age and cognitive skills for paediatric power mobility: a qualitative study. (17th August 2020) - Kenyon, Lisa K.; Jones, Maria; Breaux, Becky; Tsotsoros, Jessica; Gardner, Tonya; Livingstone, Roslyn
Abstract: Purpose: To explore the views of paediatric occupational therapists and physical therapists in Canada and the USA related to (1) the rationale for the age at which power mobility is considered for children and (2) the cognitive skills considered when trialling power mobility. Materials and methods: This study was part of a larger web-based survey study and analyzed responses to two open-ended survey questions: one related to age and one related to cognitive skills. Data were analyzed using the constant comparative method. Results: Analysis revealed four unique themes in the question related to age: (1) 'Power Mobility Should be Introduced at a Specific Age or Stage'; (2) 'Child Requirements'; (3) 'Developmental Impact of All Forms of Independent Mobility'; and (4) 'Benefits of Power Mobility'. In the question concerning cognitive skills, two unique themes were identified: 'Cognitive Skill Requirements?' and 'Non-Cognitive Requirements'. Two additional themes were identified in both questions: ('Non-child Requirements' and 'Power Mobility Trials, Use, and Options Are Dependent on Age and Goal'). Conclusions: Data indicate wide variability in respondents' views related to the provision of power mobility. Additional research is needed to explore both therapists' reasoning regarding power mobility use for children and how to best facilitate knowledge translation in this area. Implications for Rehabilitation: Wide variability exists related to the provision of power mobility for children. Children's age or stage in life influences therapists' consideration of power mobility. Many respondents considered cognitive skills when trialling power mobility but some did not.